2020
DOI: 10.1016/j.jiph.2020.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Chinese children and adults with RT-PCR positive COVID-19: A systematic review

Abstract: Background The various clinical manifestations of COVID-19 with RT-PCR positive patients have been reported. However, the differences in the clinical presentation between children and adults were unclear. Thus, we aimed to investigate the differences in the clinical manifestations and imaging characteristics between Chinese children and adults with COVID-19 by systematically analyzing the data derived from some latest literatures. Methods An extensive search of COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…The great majority of studies included in all reviews were from China, with studies also from Italy, Spain, South Korea, Malaysia, Singapore, Vietnam, Iran and the USA. Eight were high quality, 11 14 15 17 19 24 27 28 7 were medium, 16 18 20-23 26 and 3 were low quality. 12 13 25 The very great majority of studies within the reviews were of hospitalised CYP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The great majority of studies included in all reviews were from China, with studies also from Italy, Spain, South Korea, Malaysia, Singapore, Vietnam, Iran and the USA. Eight were high quality, 11 14 15 17 19 24 27 28 7 were medium, 16 18 20-23 26 and 3 were low quality. 12 13 25 The very great majority of studies within the reviews were of hospitalised CYP.…”
Section: Resultsmentioning
confidence: 99%
“…No reviews specifically focused on symptoms or signs amongst community samples of infected children, and none compared symptoms in hospitalised compared with non-hospitalised children. One review included only studies of infants 16 , one included a comparison of symptoms in children with those in adults from China, 26 and one examined only gastrointestinal symptoms. 28 One study provided descriptive data from included studies only and did not report pooled estimates of symptom prevalence.…”
Section: Resultsmentioning
confidence: 99%
“…We included 18 reviews in our analysis. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Characteristics of the included reviews are shown in table 1; all are freely available online (see online supplemental appendix table 2). All reviews were in English.…”
Section: Resultsmentioning
confidence: 99%
“…No reviews specifically focused on symptoms or signs among community samples of infected children, and none compared symptoms in hospitalised compared with non-hospitalised children. One review included only studies of infants, 16 one included a comparison of symptoms in children with those in adults from China 26 and one examined only gastrointestinal symptoms. 28 One study provided descriptive data from included studies only and did not report pooled estimates of symptom prevalence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation